Consultation for total pain in high-risk obstetrics. Issue 1 (24th August 2017) - Mackie-Jenkins, Warren; Tosca, Regina M; Groninger, Hunter
Abstract : Palliative care (PC) consultation rarely takes place in the clinical setting of high-risk obstetrics, where 'total pain' may be undermanaged. Here, we present a case of a young woman carrying twins and hospitalised for acute abdominal pain. Workup for her pain revealed non-viable fetal tissue positioned in the uterine horn; the remaining fetus was viable. Initial attempts to control the patient's pain with strong parenteral opioids by the obstetrics team and the acute pain service failed. The PC service was consulted to assist. Applying a customary interdisciplinary approach in a novel PC clinical setting, the PC service was able to identify and attend to the patient's physical, psychosocial and spiritual pain, resulting in an overall decrease in reported pain scores, decreased opioid requirement and a plan for preservation of the viable fetus.